Uji Asumsi Proportional Hazard pada Faktor yang Mempengaruhi Waktu Tahan Hidup Pasien Kanker Paru - Elnatan Dimas Aditya; Sri Sulistijowati Handajani; Ririn Setiyowati (Indonesian Journal of Applied Statistics, 2018)
Lung cancer is the disease that its death risk always increase, because of that the survival time of its patient is interesting to be researched. One of the method that can be used to research survival time of lung cancer patient is Cox regression. It has an assumption that called proportional hazard assumption. Proportional hazard assumption can be tested by graph method that is log-log graph, but the result is only used as temporary suspicion. For a better result, the goodness of fit test can be used by calculate the correlation between rank of survival time and schoenfeld residual. The result is age variabel doesn’t satisfy proportional hazard assumption. Keywords : cox regression; proportional hazard assumption; log-log graph; goodness of fit test.